The Temporary Safe Haven - An Australian Perspective - King, Jackie (Refuge: Canada's Journal on Refugees, 2001)
Australia's decision to provide temporarysafe haven protection to 4000Kosovars in response to the UNHCRrequest for assistance in their humanitarianevacuation from refugee campsin surrounding countries, requiredquick action by the government to providefor an unprecedented legislativeand service delivery framework. Thispaper looks at the notion of temporaryprotection, both in international andspecifically Australian context, beforedescribing and assessing the legislativeand service delivery mechanisms thatfacilitated Australia's response. Thispaper concludes that the risk of selectiveintepretation of the legislation andthe denial of democratic rights to thesubjects of legislation, and the less thanadequate service delivery to theKosovars, and the arguable breach of itsinternational obligations, suggests thatAustralia will have to think twice beforeengaging in such a mechanism in thefuture.